Dampak Yuridis dari Pergantian Jenis Kelamin Terhadap Status Perkawinan di Indonesia - Muhammad Firman; Gathan Lauzza Al Farizi (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the legal implications of sex reassignment on marriage status in Indonesia, focusing on the friction between civil law and Islamic law. Using a normative-juridical approach with statute and conceptual approaches, this study examines how state administration recognizes transsexual individuals and the subsequent legal protection for affected parties. The results indicate that while the state accommodates gender identity changes in population documents based on court decrees, the Marriage Law strictly enforces biological heterosexuality. Consequently, new marriages involving transsexual individuals contain an inherent material defect (error in persona) and are legally void. For sex reassignments occurring during an ongoing marriage, the legal remedy is marriage annulment (annulment/faskh) rather than standard divorce. This process retroactively renders the marriage void ab initio, affecting joint property distribution, while still protecting the civil status of children born prior to the decree. Furthermore, a dualism exists between District Court decrees and Islamic law norms in the Compilation of Islamic Law (KHI). Under Islamic law, sex reassignment without medical urgency is prohibited, meaning the original biological status quo remains effective. Thus, synchronization of specific regulations is urgently required to guarantee legal certainty and justice for all citizens.